Plant Species Richness and the Root Economics Space Drive Soil Fungal Communities - Hennecke, Justus; Bassi, Leonardo; Albracht, Cynthia; Amyntas, Angelos; Bergmann, Joana; Eisenhauer, Nico; Fox, Aaron; Heimbold, Lea; Heintz‐Buschart, Anna; Kuyper, Thomas W.; Lange, Markus; Pinheiro Alves de Souza, Yuri; et al. (Ecology letters, 2025)
ABSTRACT Trait‐based approaches have been increasingly used to relate plants to soil microbial communities. Using the recently described root economics space as an approach to explain the structure of soil‐borne fungal communities, our study in a grassland diversity experiment reveals distinct root trait strategies at the plant community level. In addition to significant effects of plant species richness, we show that the collaboration and conservation gradient are strong drivers of the composition of the different guilds of soil fungi. Saprotrophic fungi are most diverse in species‐rich plant communities with ‘slow’ root traits, whereas plant pathogenic fungi are most diverse and abundant in communities with ‘fast’ and ‘DIY’ root traits. Fungal biomass is strongly driven by plant species richness. Our results illustrate that the root economics space and plant species richness jointly determine the effects of plants on soil fungal communities and their potential role in plant fitness and ecosystem functioning. Soil fungi are critical for plants and ecosystems but are also affected by the vegetation itself. Here, we show how an experimental gradient of plant species richness and community fine root traits drive the diversity and abundance of soil fungal guilds. We highlight that fungal biomass is determined by plant biomass and plant species richness, whereas the diversity and relative abundance of individual fungal guilds are linked to the fine root traits of the plant community.